Inventory Turnover as a Conduit: Sales Growth, Capital Structure, and Profitability - Siti Mira Mutiah; Mudawanah, Siti; Pindonta Nalsal Purba (LP3kM Buddhi Dharma University, 2026)
This study aims to examine the impact of sales growth and capital structure on profitability, with inventory turnover positioned as a mediating variable, in food and beverage companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Using a quantitative explanatory design, this study applies panel data regression with path analysis to evaluate both direct and indirect relationships among the variables. Model selection was conducted through the Chow test, Hausman test, and Lagrange Multiplier test, while the mediation effect was assessed using the Sobel test. The results show that sales growth has a positive and significant effect on inventory turnover and profitability. In contrast, capital structure has no significant effect on inventory turnover but negatively affects profitability. Inventory turnover is found to negatively affect profitability and does not mediate the relationships between sales growth and profitability or between capital structure and profitability. Theoretically, these findings challenge the conventional assumption that faster inventory turnover necessarily strengthens profitability or serves as an effective transmission mechanism between financial decisions and firm performance. Instead, profitability is more directly influenced by sales expansion and the debt structure. Practically, this study provides insights for financial managers to control leverage, protect profit margins, and align inventory policies with pricing and demand strategies. The findings also assist investors in evaluating firm performance by considering sales growth, capital structure, and operational efficiency simultaneously.